Charting Spiritual Care The Emerging Role of Chaplaincy Records in Global Health Care - Peng-Keller, Simon; Neuhold, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This open access volume is the first academic book on the controversial issue of including spiritual care in integrated electronic medical records (EMR). Based on an international study group comprising researchers from Europe (The Netherlands, Belgium and Switzerland), the United States, Canada, and Australia, this edited collection provides an overview of different charting practices and experiences in various countries and healthcare contexts. Encompassing case studies and analyses of theological, ethical, legal, healthcare policy, and practical issues, the volume is a groundbreaking reference for future discussion, research, and strategic planning for inter- or multi-faith healthcare chaplains and other spiritual care providers involved in the new field of documenting spiritual care in EMR. Topics explored among the chapters include: Spiritual Care Charting/Documenting/Recording/Assessment Charting Spiritual Care: Psychiatric and Psychotherapeutic Aspects Palliative Chaplain Spiritual Assessment Progress Notes Charting Spiritual Care: Ethical Perspectives Charting Spiritual Care in Digital Health: Analyses and Perspectives Charting Spiritual Care: The Emerging Role of Chaplaincy Records in Global Health Care is an essential resource for researchers in interprofessional spiritual care and healthcare chaplaincy, healthcare chaplains and other spiritual caregivers (nurses, physicians, psychologists, etc.), practical theologians and health ethicists, and church and denominational representatives.
Chapter 1. Introduction -- Chapter 2. A Short History of Documenting Spiritual Care -- Chapter 3. Chaplaincy Documentation in a Large U.S. Health System -- Chapter 4. The Quebec Model of Recording Spiritual Care: Concepts and Guidelines -- Chapter 5. Charting and Documenting Spiritual Care in Health Services: Victoria, Australia -- Chapter 6. Spiritual Care Charting/Documenting/Recording/Assessment: A Perspective from the United Kingdom -- Chapter 7. Spiritual Care and Electronic Medical Recording in Dutch Hospitals -- Chapter 8. The Spiritual Caregiver as a Bearer of Stories: A Belgian Exploration of the Best Possible Spiritual Care from the Perspective of Charting -- Chapter 9. Charting in Switzerland: Developments and Perspectives -- Chapter 10. Charting Spiritual Care: Psychiatric and Psychotherapeutic Aspects -- Chapter 11. Palliative Chaplain Spiritual Assessment Progress Notes -- Chapter 12. Charting Spiritual Care: Ethical Perspectives -- Chapter 13. Charting Spiritual Care in Digital Health: Analyses and Perspectives.
Keywords: Medical care; Religion and sociology; Psychology and religion; Bioethics; Health Care; Sociology of Religion; Psychology of Religion and Spirituality; Bioethics